The mental rotation ability of expert basketball players: Identifying on-court plays - Weigelt, M.; Memmert, D. (Research Quarterly for Exercise and Sport, 2021)
Purpose: The purpose was (1) to test a new version of a mental rotation task (MRT), which assesses mental rotation abilities of men and women for sport-specific items, and (2) to investigate potential differences in MRT performance, which are based on athletic expertise. Methods: Eighty-eight basketball experts (42 females) and 123 novices (64 females) were tested with a paper-and-pencil version of the "Mental Rotation Task—Basketball (MRT-BB)", which is similar to the original MRT. Instead of three-dimensional cubes, six different basketball plays were used as stimuli. The criterion stimulus of the 24 items was always displayed in an upright orientation (basket on top), located on the left side of the sheet. In addition, two "correct" alternatives (one stimulus rotated by 90° to the left or right and one by 180°) and two "incorrect" alternatives (either rotated mirror-images of the criterion stimulus or rotated images of a different play) were displayed in different positions of the same row. The task was to identify the "correct" alternatives. Results: Results demonstrated (a) an effect of sex, with more items solved for male participants as compared to female participants, and (b) an effect of expertise, with better performance of expert players than of novices. Conclusions: Male and female basketball experts show better mental rotation skills for sport-specific stimulus material. The MRT-BB extends standard tests of mental rotation to sport-specific stimulus material and can be used to test the sport-specific mental rotation skills of basketball players.